1996
DOI: 10.1111/j.1523-5378.1996.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection in Congestive Gastropathy

Abstract: We conclude that the role of H. pylori in the pathogenesis of congestive gastropathy is unlikely, and we suggest that there is no need for its routine eradication in cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…This gastric manifestation of portal hypertension is present in up to 50% of cirrhotic patients (20), and accounts for one-third of bleeding events in these patients (21). In the present study, the prevalence of H pylori infection was similar in patients with congestive gastropathy compared with patients without (42% versus 46%), as previously demonstrated (22,23), and peptic ulcer disease was slightly more prevalent among H pylori-infected patients with congestive gastropathy than in infected patients without congestive gastropathy. Overall, observations from the literature seem to indicate that congestive gastropathy and H pylori infection are independent factors that may affect the gastric mucosa.…”
Section: Discussionsupporting
confidence: 89%
“…This gastric manifestation of portal hypertension is present in up to 50% of cirrhotic patients (20), and accounts for one-third of bleeding events in these patients (21). In the present study, the prevalence of H pylori infection was similar in patients with congestive gastropathy compared with patients without (42% versus 46%), as previously demonstrated (22,23), and peptic ulcer disease was slightly more prevalent among H pylori-infected patients with congestive gastropathy than in infected patients without congestive gastropathy. Overall, observations from the literature seem to indicate that congestive gastropathy and H pylori infection are independent factors that may affect the gastric mucosa.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies failed to find a correlation between the severity of PHG and H. pylori infection. [ 24 25 26 ] During advanced gastropathy, the environment for the colonization of H. pylori becomes unfavorable, resulting in a decrease in the number of patients harboring this organism. In our study, the patients harboring H. pylori were of younger age, had higher serum albumin, lower Child Pugh score, and lower portal vein diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies were identified after additional searches. Finally, 13 studies (8 cohort studies and 5 case-control studies) were included in the meta-analysis [10][11][12][13][15][16][17][18][19]24,25]…”
Section: Literature Searchmentioning
confidence: 99%